Relevansi Konsep Hadhanah dalam Hukum Keluarga Islam Kontemporer: Kajian Literatur - Hendriko Hendriko (Kampus Akademik Publiser, 2025)
This research aims to explore the relevance of the concept of Hadhanah in contemporary Islamic Family Law through a literature review. The concept of Hadhanah, closely related to the family's responsibility in managing wealth and assets, has a significant impact on family dynamics in modern society. This study analyzes the evolution of the Hadhanah concept over time and its role in the context of contemporary Islamic family law. The research employs a descriptive-analytical approach with a focus on the analysis of literature texts related to the concept of Hadhanah in Islamic Family Law. Data is obtained through a literature review and comprehensive analysis of relevant literature, including Islamic legal texts, scholarly papers, and related publications. The research findings indicate that the concept of Hadhanah remains relevant in contemporary Islamic Family Law. In today's complex society, the role of the Hadhanah concept as a legal principle governing ownership, management, and distribution of family wealth remains of significant importance. The study also identifies changes and adaptations in the concept of Hadhanah in response to social and economic changes. This research provides valuable insights into the understanding of the Hadhanah concept in the context of modern Islamic family law and serves as a foundation for further discussions on how this concept can be effectively applied in the lives of families and society today.